Homework Research, Policy, and Implementation - Foyle, Harvey C.; Lyman, Lawrence ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
This paper discusses homework policy as a product of 50 years of experimental research. Part 1 discusses homework guidelines in grades 3 through 8 by suggesting that homework should be assigned, graded, and individualized. In addition, homework should provide feedback about student achievement that includes parental monitoring. Part 2 recommends secondary school homework policies that include clear and concise graded assignments. Furthermore, the proposal that some homework be guided, voluntary, and nonwritten reflects outcomes of homework research in American education. The conclusion that the assigning of homework should follow a regular pattern aligned with classroom subject matter supports the notion that homework reinforces learning, thereby raising student achievement. Moreover, school districts should support homework policies that research findings link to raising student achievement. (JAM)
ERIC Note: Paper presented at the Annual Meeting of the Association for Supervision and Curriculum Development (44th, Orlando, FL, March 11-14, 1989).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Assignments; Educational Assessment; Educational Methods; Educational Policy; Educational Practices; Educational Research; Elementary Education; Guidelines; Homework; Theory Practice Relationship; Speeches/Meeting Papers; Information Analyses; Opinion Papers